Study of Language Contacts by Linguists - Vositov Volijon Abduvaxobovich (Zien Journals, 2022)
The article deals with the study of language contacts by linguists, its broad interpretation, conditions and connections of language contacts, the degree of foreign language influence in different languages, intra linguistic and extra linguistic factors, the types of AngloTurkic language contacts. Here the author gave more information on the study of the problem of language contacts has a long tradition both in foreign and domestic linguistics, although the term "language contacts".
Keywords: language contacts; dialects; bilingualism